Evaluation of physicochemical parameters of water samples around proposed Nuclear Power Plant (NPP) in Kovvada, Srikakulam District, Andhra Pradesh, India. (2022) - Mamidi, Yugandhar; Subba Reddy, Gopireddy V.; Ramarao, D.; Sahoo, S.K.; Lokesh, Budigi; Gadamsetty, Ganesh; David, Ezhumalai
Abstract: The present study was targeted for describing water quality of surface and subsurface in and around proposed Kovvada Nuclear Power Plant (NPP) which is nearby seacoast of Srikakulam district, Andhra Pradesh. Water samples were collected according to BRNS protocols during pre- and post-monsoon period. The water quality parameters such as pH(6.4–8.3 and 6.8–8.2), TDS(102–3425 and 102–3425 ppm), Electrical Conductivity1(64–5561 and146-4911 µS/cm), Salinity(73–2576 and 78–2311 ppm), Dissolved Oxygen(3.7–8.3 and 4.4–8.9 ppm), Total Alkalinity (TA) (20–790 and 10–730 ppm), Total Hardness (TH)(45–1110 and 20–990 ppm), Chloride(7–2006 and 4.9–1994 ppm), Nitrate(2.7–74.2 and 3.0–77.5 ppm) Fluoride(0.11–2.13 and 0.07–2.39 ppm), Sulphate(4–364 and 8–360 ppm) was measured in both Pre and Post-monsoon seasons. The estimated water quality parameters were compared with the world health organization (WHO) and Bureau of Indian Standards (BIS). The obtained numerical data showed that most of the water samples in this area are lower than WHO and BIS standards. Few samples are exceeding limits in characteristics like TDS, TA, TH, Chloride, Nitrate due to the locations that are nearby Bay of Bengal. The obtained data would act as a bench mark database for future reference of NPP.